Resolution of industrial disputes in New Zealand - Ali Mohamed, Ashgar Ali (Centre for Promoting Ideas, USA, 2012)
Workplaces dispute should ideally be resolved through collaborative and less confrontational means. Mediation is the best dispute resolution process. Apart from providing fast, creative and mutually satisfactory resolutions, mediation has the potential of preserving the relationship between the parties. Mediation can mend and preserve frayed working relationships, even when the parties are extremely angry. Moreover, mediation fosters mutual respect through improved communication. The Employment Relations Act 20002 (ERA), the current employment statute of New Zealand, emphasised inter alia, mediation as the primary problem-solving mechanism of labour disputes. Under the ERA, wherever an employment relationship problem arises, the parties would be encouraged to attempt to resolve their disputes voluntarily through discussions amongst themselves. Alternatively, the parties may seek mediation services provided by the Department of Labour. Meanwhile, the adjudication of the dispute falls within the jurisdiction of the Employment Relations Authority (hereinafter referred to as the Authority).3 The Authority is also empowered to refer the parties to the labour disputes for mediation. Having said the above, this article examines the use of mediation as a mechanism of resolving labour disputes in New Zealand.